Complying with genocide: the wolf you feed - Anderson, E. N. (Lexington Books, 2021)
Part I: Mass Killing: The Story of Complicity -- Part II: The Roots of Human Evil -- Part III: The March of Genocide: Past and Present -- Part IV: Which Wolf Will We Feed?